PENGARUH LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR PPKn SISWA KELAS XI SMAS KARYA PENGALIHAN KABUPATEN INDRAGIRI HILIR - Siti Nurjannah; Hambali; Indra Primahardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by low student learning achievement, this is in line and can be seen from the phenomenon where most students show behavior when observed from the way students learn, there are still playful while studying such as chatting with friends and not taking notes of the material presented by the teacher. The purpose of this study was to determine whether there is an influence of the school environment on the learning achievement of PPKn class XI students. This study uses a quantitative method with a survey method with a causal associative nature. The population in this study were class XI students of SMAS Karya Pengalihan, Indragiri Hilir Regency. Determination of the sample using the Slovin formula with a random sampling technique with a level of 5% so that the number of samples was 99 respondents. The research instrument used was a questionnaire with 19 statements. Based on the statistical test, it was obtained that the Fcount value ≥ Ftable (78.648 ≥ 3.94) and a significant value of 0.000 ≤ 0.05. So it can be concluded that Ho is rejected and Ha is accepted, so that the School Environment (Variable X) has a significant effect on Learning Achievement (Variable Y). The results of the analysis of the coefficient of determination test of the influence of the school environment (X) on learning achievement (Y) were 44.8%, while 55.2% was influenced by other variables that were not examined in this study.